The Behavior of Worker Cooperatives: The Plywood Companies of the Pacific Northwest - Craig, Ben; Pencavel, John (American Economic Review, 1992)
Using data collected by the authors on the largest and most durable of worker-owned firms in U.S. manufacturing, this paper is addressed to two questions. First, are the responses of cooperatives to changes in their economic environment different from those of conventional firms? It appears that cooperatives are more inclined to adjust pay than employment. Second, how profitable has membership in the cooperatives been? Using information on share prices, we find membership to have been extremely profitable, and in this sense, the prices of co-ops' shares have been underpriced. The riskiness of cooperative membership is discussed.